FGF21 as a Hepatokine, Adipokine, and Myokine in Metabolism and Diseases - Itoh, Nobuyuki (Frontiers in Endocrinology, 2014)
Fibroblast growth factor (FGF) family members are mostly secreted as signaling proteins with diverse functions in development and metabolism. FGF21 is a unique FGF with metabolic, but not proliferative activities. FGF21 is mostly induced by different kinds of stress and acts though FGF receptor 1c with β-Klotho as a cofactor in an endocrine or, in parts, autocrine/paracrine manner. Hepatic FGF21 directly acts on white adipocytes to inhibit lipolysis and acts through the brain to increase systemic glucocorticoid levels and suppress physical activity in response to starvation. It also protects against dioxin toxicity. Adipocytic FGF21 induces the browning of white adipose tissue (WAT) and activates brown adipocytes in response to cold exposure. It also acts as an upstream effector of adiponectin in white adipocytes. Myocytic FGF21 protects against diet-induced obesity and insulin resistance, induces the browning of WAT, and protects against cardiac hypertrophy. In addition, Fgf21 polymorphisms are possibly related with metabolic diseases and FGF21 are biomarker of metabolic diseases. These findings indicate that FGF21 plays roles as a hepatokine, adipokine, and myokine in metabolism, injury protection, and diseases.